The impact of water stress at key phenological stages on yield and quality of pecans (Carya illinoinensis Wangenh. K.Koch) - Taylor, Nicolette Jane (University of Pretoria, 2022)
Dissertation (MScAgric (Horticulture))--University of Pretoria, 2021.